Enhancing Community Self-Empowerment Through the Magnet Rezeki Hybrid Seminar in Bukit Raya - Masnur Putra Halilintar; Sunengsih (SocietalServe: Journal of Community Engagement and Services, 2025)
The Hybrid Magnet Rezeki Seminar, conducted in February 2025 in Bukit Raya District, represents a faith-based community empowerment initiative focused on enhancing individuals’ self-capacity through spiritual and practical development. Anchored in the broader framework of the Magnet Rezeki Outreach Program, this initiative introduced participants to core principles such as Disiplin Kata (Word Discipline), Law of Projection (LOP), and Perisai Rezeki (Wealth Shield). Implemented through an interactive and reflective learning model, the seminar engaged 28 participants with the support of Certified Trainers of Magnet Rezeki (CTMR). Pre- and post-test evaluations revealed significant improvements in participants’ comprehension and mindset regarding spiritual empowerment and ethical financial behavior. The program's outcomes demonstrated its alignment with national objectives in sustainable human resource development, particularly in the integration of Islamic values into practical life skills. This study underscores the potential of hybrid-format, faith-driven seminars to foster lasting personal growth and community resilience. Furthermore, it opens pathways for replicating similar models in other local contexts to advance spiritually grounded economic empowerment.